PRODUCTIVITY AND BONE QUALITY OF BROILERS SUPPLEMENTED WITH VITAMIN D (25-OHD3) - Araujo Baldo, Grace Alessandra; Correia de Lima Almeida Paz, Ibiara; Garcia, Edivaldo Antônio; de Britto Molino, Andréa; Correia de Lima Almeida, Ianê (ENERGIA NA AGRICULTURA, 2017)
Problems with broilers bone quality are becoming more frequent and alternatives have been sought to reduce them without altering poultry performance. The experiment was conducted to assess the productivity and bone quality of broilers supplemented with 25-OHD3. A total of 2400 broilers were distributed in randomized block design with 2x2x2 factorial arrangement (gender, Cobband Ross strains, supplemented or not with 25-OHD3), totaling eight treatments with six repetitions of 50 birds each. Birds’ performance, gait score and bone quality (Seedor index, bone resistance, bone ash, minerals levels (Ca, P and Mg) and black bone syndrome) were evaluated. There was interaction between gender and strains for feed intake and weight gain; the feed conversion ratio was better for males; there was an interaction between strain and supplementation for viability. There was a difference in gait score for gender and strain. Males femur had a higher Seedor index, bone resistance and lower ashes level. Ross strain showed higher Seedor index. Regarding tibia ash levels in and femur Mg content, there was strain and supplementation interaction. Black bone syndrome was not influenced by the studied variables. Some of the assessed characteristics had positive responses and others characteristics discreetly responded to the treatments. KEYWORDS: Animal performance, black bone syndrome, bone resistance, gait score, Seedor index. PRODUTIVIDADE E QUALIDADE ÓSSEA DE FRANGOS DE CORTE SUPLEMENTADOS COM VITAMINA D (25-OHD3) RESUMO: Problemas com a qualidade do osso de frangos de corte estão cada vez mais frequentes e tem se buscado alternativas para redução dos mesmos sem alteração do desempenho das aves. O experimento foi conduzido com o objetivo de avaliar a produtividade e a qualidade óssea de frangos de corte suplementados com 25-OHD3. Foram utilizados 2.400 frangos distribuídos em blocos casualizados com esquema factorial 2x2x2 (gêneros, linhagens CobbeRoss, suplementadas ou não com 25-OHD3), totalizando oito tratamentos com seis repetições de 50 aves cada. O desempenho, gait score e qualidade óssea (índice Seedor, resistência, cinzas, níveis de minerais (Ca, P e Mg) e síndrome do osso negro) foram avaliados. Houve interação sexo linhagem para o consumo de ração e o ganho de peso; a conversão alimentar foi melhor para os machos; houve interação linhagem suplementação para viabilidade. O gait score foi diferente entre sexos e linhagens. Para o fêmur os machos apresentaram maior índice Seedor, resistência óssea e cinzas. A linhagem Ross apresentou maior índice Seedor e houve interação linhagem suplementação para cinzas na tíbia, bem como para o teor de Mg no femur. A síndrome do osso negro não foi influenciada pelas variáveis estudadas. Conclui-se que algumas características avaliadas apresentaram respostas positivas e outras responderam discretamente aos tratamentos. PALAVRAS-CHAVE: Desempenho animal, gait score, índice Seedor, resistência óssea, síndrome do osso negro.